2021
DOI: 10.24052/bmr/v12nu01/art-09
|View full text |Cite
|
Sign up to set email alerts
|

Electricity outages and its effect on small and medium scale enterprises (SMEs) in Nigeria

Abstract: Constant electricity supply enhances smooth running and performances of SMEs. However, electricity outages in Nigeria have been identified as one of the factors hindering SMEs’ performance. This study aimed at exploring the impact of electricity outages on the operations and contributions of SMEs to Nigeria economy. Hence, the study evaluated the impacts of electricity supply on the growth of SMEs in Nigeria. It analysed the hindrances that deficient electricity supply could have on the growth and development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The association between using informal sources of financing and the financial performance of SMEs is inconclusive. The cost of informal debt can be lower than formal debt since relationship and reputational aspects can be beneficial for owners borrowing through informal sources (Adanlawo, 2021). An opposing argument is that informal debt, particularly from friends and family, can create shadow costs that eventually undermine the utility of such sources of financing (Lee & Persson, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between using informal sources of financing and the financial performance of SMEs is inconclusive. The cost of informal debt can be lower than formal debt since relationship and reputational aspects can be beneficial for owners borrowing through informal sources (Adanlawo, 2021). An opposing argument is that informal debt, particularly from friends and family, can create shadow costs that eventually undermine the utility of such sources of financing (Lee & Persson, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The increased risk due to informal financing could negatively impact a firm’s performance; however, the literature is also inconclusive in this regard. On one hand, the literature views informal financing as beneficial in reducing the cost of borrowing through relationships with friends, family, and other informal lenders (Adanlawo, 2021). Conversely, research has also suggested informal financing costs can be higher due to the shadow costs of these very relationships, such as social obligations owed to family members in case of default (Lee & Persson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This figure went up to 834 in the following year, all because of poor electricity power supply and high cost of the alternative energy supply. More so, Adanlawo and Vezi-Magigaba (2021) examuined the effects of electricity outages on the operations of Small-Scale enterprises in Nigeria. The descriptive survey design was employed to administer structured questionnaires to SMEs operators in Lagos state, Nigeria.…”
Section: Electricity Load Shedding and Business Operations Of Small-s...mentioning
confidence: 99%
“…The second category of workers is referred to as "non-engaged employees," and they are not enthusiastic or active at their place of work (Adanlawo, Vezi-Magigaba & Owolabi, 2021;Johnston et al, 2019). Fitawek et al (2020) claim that these personnel are primarily focused on objectives and task execution.…”
Section: Literature Reviewmentioning
confidence: 99%